Community ontogeny at the roadside: Critical life‐cycle events throughout a sequential process of primary colonization. Issue 3 (29th January 2014) - Magro, Sandra; Jiménez, María Dolores; Casado, Miguel Angel; Mola, Ignacio; Arenas, Juan Maria; Martín‐Duque, Jose Francisco; Vazquez, Ana; Balaguer, Luis; Ohlemuller, Ralf
Abstract Questions How does the response to environmental filters change across the life cycle of pioneer plants through the early process of community assembly? Is there a threshold at any of the life‐history stages during roadcut primary colonization? Location A very steep, sun‐exposed, low‐fertility and low water retention roadcut in a Mediterranean continental site in Madrid, central Spain. Methods We tracked density of individuals, plant cover, species richness and community composition throughout the sequential process of primary colonization of a newly‐exposed roadcut surface. We monitored from seed arrival to seedling emergence, seedling survival and plant growth across species over two growing seasons. We manipulated the intensity of environmental filters in 12 experimental plots (10 × 8 m) following a full‐factorial design of two treatments (topsoil spreading and shallow tillage). Results The response to environmental filter manipulation varied throughout the individual life cycle. Under an equal seed rain, the higher carrying capacity caused by topsoil spreading gave rise to the emergence of a larger number of species, which either persisted or occasionally appeared in some of the stages of the early community assembly. Further, topsoil spreading enhanced seedling survival across species, as well as subsequent plant growth. We therefore detected two life‐history stages acting as thresholds in plant community assembly due to an ontogenetic niche shift across species. The first, at seedling emergence, in response to environmental cues with lasting consequences in community composition and species richness; and the second, at the transition to the adult stage in response to local resource availability, with consequences in subsequent plant growth and community cover. Conclusions During primary colonization, ontogenetic development of pioneers was paralleled by the action of environmental filters throughout the community assembly process. On roadcuts, the confluence of both processes gives rise to a community ontogeny marked by two thresholds determining community richness and cover under Mediterranean conditions. Our findings shed light on the underlying mechanisms involved in technical solutions, such as topsoil spreading, and provide a more efficient approach to roadside restoration.